ANALISA PENGARUH ACCOUNTING INFORMATION SYSTEM TERHADAP COMPETITIVE ADVANTAGE MELALUI KNOWLEDGE MANAGEMENT PADA INDUSTRI PERHOTELAN DI SURABAYA - Arie Widiharta; Saarce Elsye Hatane (Business Accounting Review, 2017)
This research was conducted to find out the influence of Accounting Information System Against competitive advantage Through Knowledge Management as intervening variable in the hospitality industry located in Surabaya. Competitive advantage became one of the most important variables that was able to measure the hospitality ability. An other variables that was accounting information system had contribution in creating competitive advantage of the company. On the other hand, the application of accounting information system could not be separated from the support of knowledge management that were in the hotel.Data analysis techniques used in this research was the partial least square to describe the relationships between variables. The research results showed that the accounting information system and knowledge management affected the competitive advantage in a positive and significant in the hospitality industry located in Surabaya.